2022
DOI: 10.1002/bin.1886
|View full text |Cite
|
Sign up to set email alerts
|

A review of response interruption and redirection: 2007–2021

Abstract: The objective of this paper is to provide a review of the current state of the literature on response interruption and intervention (RIRD) beginning with the year the term was first coined. The paper aims to replicate and refine previous reviews on this topic by including: (1) only articles that used the term “RIRD”; (2) all behaviorally oriented journals with publications on the topic; (3) articles that evaluated RIRD across multiple topographies of automatically reinforced behavior; and (4) an evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…As in previous reviews (Mantzoros et al, 2022;Martinez & Betz, 2013;Ryan et al, 2022), the current review found limited reports of social validity data. Given behaviors maintained by automatic reinforcement are often selected based on the acceptability of those behaviors in the individual's given environment, it may behoove researchers and clinicians alike to collect social validity data on the goals and procedures across settings where the behavior occurs and intervene only where warranted.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As in previous reviews (Mantzoros et al, 2022;Martinez & Betz, 2013;Ryan et al, 2022), the current review found limited reports of social validity data. Given behaviors maintained by automatic reinforcement are often selected based on the acceptability of those behaviors in the individual's given environment, it may behoove researchers and clinicians alike to collect social validity data on the goals and procedures across settings where the behavior occurs and intervene only where warranted.…”
Section: Discussionmentioning
confidence: 89%
“…Mantzoros et al (2022) reviewed the literature for vocal stereotypy and emphasized the efficacy of RIRD as a solitary procedure. Most recently, Ryan et al (2022) conducted a review of RIRD applications between 2007 and 2021 that included categories for several important considerations, such as inclusion of maintenance data and social validity measures.…”
mentioning
confidence: 99%
“…Response interruption and redirection 4 procedures were used to reduce SIB while data tracking was completed. Parent's attempts to put goggles or mitts on the patient or block SIB attempts resulted in patient and parent injury.…”
Section: Christina Low Kapalu Phdmentioning
confidence: 99%
“…Response interruption and redirection (RIRD) has been shown to be an effective behavioral treatment for stereotypy (e.g., Ahearn et al, 2007; Athens et al, 2008; Cassella et al, 2011), although most evaluations have targeted vocal stereotypy (Ryan et al, 2022). This procedure involves the interruption of stereotypic responses by presenting contingent instructions that prompt the individual to engage in vocal or motor responses.…”
mentioning
confidence: 99%